Portrait of Outstanding Alumnae: Basis for Career Guidance Program - Gamboa, Alberto G.; Gamboa, Jerame N.; Mercado, Plato B.; Nicdao, Criselda G.; Puebla, Joan N. (Future Science / FSH-PH Publications, 2022)
The study aims to describe how the graduates from a state university and college in Region III, Philippines excel in their chosen careers. The findings of the study can be a source of model or inspiration to the students as well basis for career guidance program which can be used to further equipped students in their field of work. Specifically, it sought to find the contributory factors to be outstanding in chosen field; what are challenges and success that the alumnae experienced as students and employees; and how do the alumnae engage with the community. The study used descriptive phenomenology.In choosing the participants, purposive sampling was utilized. From the set criteria in choosing the participants, 11 were identified. The study used open-ended questionnaire. It was found out that to be outstanding, trainings, learnings, and values are necessary; however challenges will be there like of low self-esteem, poverty, losing a loved one, expectations and self-doubt. But the fruits of it is sweeter, such as winning, passing and top notching licensure examinations, receiving awards/recognitions, being promoted, and owning a business. But being outstanding must be shared by doing volunteer works to the community, helping the poor, and inspiring others. Based on the findings of the study, inclusion of being employable and being serviceable in the career guidance program is suggested. Further, invitations of successful alumnae will be a great motivation to the students. And further conduct of the study may be done to have a comprehensive description of an outstanding graduate of a different or wide locale.